Diet modulates host health through gut microbiota derived extracellular vesicles: A short review - Xin Feng; Caiyu Luo; Jianwei Che (Aceh Journal of Animal Science, 2023)
Gut microbes are involved with many host physiological processes including digestion, metabolism, immune response, gut function and behavior. Among all the factors, diet is being considered the most important one to modulate gut microbiota composition, metabolism and their metabolites. Extracellular vesicles (EVs) are secreted to the intestinal environment by gut microbes and play an essential role in gut microbe-host communication. This paper aims to review how diet affects gut microbial EVs and its composition as well as how this change further affects host health. This review summarizes the latest research progress of interaction among diet, gut microbial EVs, and host health. Through the microbiota-gut axis, gut microbial EVs involve in many physiological activities, including brain function, metabolism, gut function and immune response. It has been verified that diet composition has direct changes on gut microbial morphology and internal molecules within gut microbial EVs. Overall, studies investigating the effects of diet through gut microbial EVs on host health are very limited. Future research regarding axis of diet-gut microbial EVs-host health is recommended.